Sangguniang Kabataan handbook for New Youth Councils - Abletez, Jose P. ([Manila] Mary Jo Pub., 1992)
It is about the Sangguniang Kabataan (SK) as a council the of youth in every barangay. It is intended to teach the youth the basics of organizational development and leadership training. SK throughout the country must be well versed on the Local Government Code and the role they and their councils and federations must play.
Contents: Rules and procedures of SK elections. Federation of SKs. SK Chair as lawmaker. Sanggunian Sessions/Meetings. SK funding support. SK Powers, Duties and Functions. Comelec Resolutions. Constitution and by-laws. DILG Recommendation on SK Polls. Senate Resolution No. 12 on SK Election Postponement. Sample Barangay Ordinance. Resolutions and Minutes of Meeting. Executive Order No. 274. Creation of PCYA. Memo Circular.
Purpose: "To guide young people in the election of the officers of their respective federations and in the pursuit of SK goals and objectives."
Keywords: Youth -- Societies and clubs -- Law and legislation; Youth -- Political activity -- Handbooks, manuals, etc